APLIKASI ANALISIS TEKNIKAL DALAM MENINGKATKAN POTENSI KEUNTUNGAN INVESTOR DENGAN MOVING AVERAGE DAN CANDLESTICK - Anggraini, Septi; Setiawan, Romi Adetio; Indra, Yetti Afrida (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine whether technical analysis, using moving average and candlestick indicators, can simultaneously influence investors' profit potential. The population in this study consists of FEBI students who opened an account in 2021, with a sample size of 71 students. The research employs a quantitative method with an associative quantitative approach. Data collection was conducted through questionnaires. The data analysis technique used is multiple linear regression to test the research hypothesis, utilizing the t-test and F-test with the SPSS 16 for Windows software application. The research results indicate that the technical analysis variables (X1), moving average (X2), and candlestick (X3) have a simultaneous influence on potential investment profits, confirming that the hypothesis is accepted.